2020
DOI: 10.1016/j.ijbiomac.2020.09.159
|View full text |Cite
|
Sign up to set email alerts
|

Characterization on chemical and mechanical properties of silane treated fish tail palm fibres

Abstract: A novel cellulosic fibre was extracted from the peduncle portion of the fish tail palm tree and the extracted fish tail palm fibre was treated with different concentrations (1%, 5%, and 9%) of silane solution. The characteristic analysis on chemical, functional, mechanical and surface property of the extracted fish tail palm fibres were investigated through chemical composition analysis, Fourier Transform InfraRed spectroscopy (FT-IR), single fibre tensile test, and Scanning Electron Microscopy (SEM). Chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…It indicates C8 silane treatment can remove hemicellulose and lignin or non-crystalline cellulose present in the ber. [19] A signi cant broad mass loss occurred between 375-750 O C in raw and C8 treated DPF, as shown in Fig. 3(B).…”
Section: Resultsmentioning
confidence: 78%
“…It indicates C8 silane treatment can remove hemicellulose and lignin or non-crystalline cellulose present in the ber. [19] A signi cant broad mass loss occurred between 375-750 O C in raw and C8 treated DPF, as shown in Fig. 3(B).…”
Section: Resultsmentioning
confidence: 78%
“…Renewable energy has therefore become more significant to achieve environment-healthy human and socioeconomic prosperity [4]. In this regard, research presents challenges in the development of green chemistry with the use of an important natural source of organic matter and accessible raw materials., to avoid ecosystem disruption [5,6]. This requires the inclusion of various products with high added value, such as the energy source, solid fuel for combustion and biofuels, as well as biomaterials like bioplastic, road binder and dye dispersant in addition to other common chemicals like propanol, acetone, succinic acid, lactic acid, pesticides and others [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The higher oxygen to carbon percentage indicates the removal of lignin and hemicellulose components from the AS particle. 27 It can be understood that the alkaline modification reduces the lignin content in AS particles without affecting the cellulose substance. Saw et al 25 observed similar observations on the effect of surface modification on the luffa fiber.…”
Section: Surface Feature and Elemental Analysis Of As Particlementioning
confidence: 99%